Methane conversion to higher hydrocarbons over W/HZSM-5-based catalysts in the presence of oxygen - Amin, Nor Aishah Saidina; Pheng, Soon Ee (Elsevier BV, 2006)
Methane conversion to higher hydrocarbons in the presence of oxygen was studied over W/HZSM-5-based catalysts. W–H2SO4/HZSM-5 catalyst containing octahedral coordinated tungsten species showed the highest activity. Over 2% W–H2SO4/HZSM-5 catalyst, the methane conversion reached ≈20% with the average aromatic yield being 9% after 200 min of time on stream. In addition, the results of methane conversion in non-oxidative condition showed that the catalytic activity was drastically reduced with time on stream. Consequently, it can be concluded that the durability of the catalysts was enhanced in the presence of suitable amount of O2.